Analisis perbandingan rencana strategis perbankan swasta potensial menurut metode Glueck - Arnanda, Putri Amalia; Ramadhani, Sri Wahyu (Maliki Interdisciplinary Journal, 2023)
Banks have a big responsibility to store, maintain and circulate money in society. Strategic plans are needed to develop and improve company performance productivity. This research aims to observe comparison of the 2022 strategic plans held by 3 banks, namely Bank Shinhan Indonesia, Bank Sinarmas, and Bank Victoria International. This research uses qualitative or descriptive qualitative data analysis methods. This study found that in each bank's strategic plan there are several differences, both in terms of long, medium and short term strategies. The most striking difference is that Bank Shinhan Indonesia did not include their long-term strategic plan in the 2022 annual report, but outlined their short-term strategic plan.